Efeito de uma intervenção multiprofissional na prevalência do aleitamento materno exclusivo em um hospital universitário - Segala, Elizamara Eliege (2016)
The World Health Organization recommends exclusive breastfeeding (EBF) until six months of age, and breastfeeding along with other foods up to two years of age or even longer. The importance of EBF until six months of age is well established, mainly because of the benefits for the child and for the mother such as a reduction in children's morbidity and mortality and also hospital admissions. Despite of the fact that breastfeeding is an effective and inexpensive way to improve child s health, unfortunately this practice is stopped long before the recommended period. Due to that, this study aimed at knowing EBF prevalence among children born at the University Hospital of Santa Maria as well as the reasons for the early weaning. Besides, it assessed the effect of a multiprofessional intervention to promote breastfeeding in the Hospital. The prevalence of EBF was assessed at four and six months postpartum in two groups: control group (whose mothers received the information usually provided by the staff) and intervention group (whose mothers received additional information about breastfeeding by a multiprofessional team). For this, a randomized trial was carried out, enrolling 379 dyads (mother-baby): 194 in the control group and 185 in the intervention group. The intervention consisted of meetings (as group dynamic) with the mothers. The results showed that EBF prevalence in the control group were 42.8% at four months, and 13.4% at six months age. On the other hand, in the intervention group the EBF prevalence was significantly higher: 57.8% at four months and 26.5% at six months age. In addition, the number of days of EBF in the intervention group was also significantly higher (median 150 days) compared to controls (median 113 days). The assessment of data at four and six months showed negative association with the variables "did not participate in the intervention" and "use of pacifiers" with the variable "duration of EBF". At six months it was further observed negative association between "duration of EBF" with mother coming back to work . The results of this study allowed us to prove the effectiveness of a multidisciplinary intervention carried out in the post-partum time in increasing EBF rates in children at the ages of four and six months.